A Triple-Blind, Placebo-Controlled Randomized Trial of the Effect of Bilateral Alternating Somatosensory Stimulation on Reducing Stress-Related Cortisol and Anxiety During and After the Trier Social Stress Test - Ernesto Cesar Pinto Leal-Junior; Heliodora Leão Casalechi; Caroline dos Santos Monteiro Machado; Amy Serin; Nathan S. Hageman; Douglas Scott Johnson (Journal of Biotechnology and Biomedical Science, 2019)
The aim of this clinical study was to determine the efficacy of bilateral alternating somatosensory stimulation for the management of stress and anxiety during and after the Trier Social Stress Test (TSST), a laboratory procedure for reliably inducing stress in human subjects. For this, a randomized, placebo-controlled, triple-blinded clinical trial of 80 qualified subjects was conducted. Subjects were randomized into two groups, a treatment group (n=40) and a control (placebo) group (n=40). Metrics of emotional stress assessed were a subjective rating of the level of emotional stress and salivary cortisol levels, both obtained at 3 timepoints: before treatment (baseline), immediately following completion of the TSST, and after 20 minutes of rest following completion of the TSST. Results showed that the treatment group had a statistically greater decrease in the subjective rating of stress relative to the control group both immediately following the TSST and 20 minutes after the TSST. Salivary cortisol levels in the treatment group were also lower than the control group at those same time points. These results suggest that bilateral alternating somatosensory stimulation may be effective in reducing subjective levels of stress and anxiety. It also may actively attenuate stress-related cortisol levels, which may reflect a mechanism for reducing cortisol-induced inflammation back to baseline after exposure to stressful situations.
Keywords: Somatosensory